2018
DOI: 10.1016/j.biomaterials.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Optimal electrical stimulation boosts stem cell therapy in nerve regeneration

Abstract: Peripheral nerve injuries often lead to incomplete recovery and contribute to significant disability to approximately 360,000 people in the USA each year. Stem cell therapy holds significant promise for peripheral nerve regeneration, but maintenance of stem cell viability and differentiation potential in vivo are still major obstacles for translation. Using a made-in-house 96-well vertical electrical stimulation (ES) platform, we investigated the effects of different stimulating pulse frequency, duration and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 51 publications
(62 reference statements)
2
90
0
2
Order By: Relevance
“…Indeed, while the Wnt signaling pathway is important in promoting symmetric division of adult neural stem cells (Adachi et al, 2007;Piccin et al, 2011Piccin et al, , 2014Azim et al, 2014;Edri et al, 2015), we demonstrate that blocking the Wnt signaling pathway was not sufficient to abolish the increase in neurospheres seen with electrical stimulation compared with control. Our findings were consistent with electrical stimulation promoting stem cell survival (Du et al, 2018), with the potential to provide an effective approach to enhance neural regeneration. Interestingly, DBS has been used in clinical setting for many years to treat advanced stages of PD, despite a paucity of knowledge related to the functional substrates that lead to benefits.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, while the Wnt signaling pathway is important in promoting symmetric division of adult neural stem cells (Adachi et al, 2007;Piccin et al, 2011Piccin et al, , 2014Azim et al, 2014;Edri et al, 2015), we demonstrate that blocking the Wnt signaling pathway was not sufficient to abolish the increase in neurospheres seen with electrical stimulation compared with control. Our findings were consistent with electrical stimulation promoting stem cell survival (Du et al, 2018), with the potential to provide an effective approach to enhance neural regeneration. Interestingly, DBS has been used in clinical setting for many years to treat advanced stages of PD, despite a paucity of knowledge related to the functional substrates that lead to benefits.…”
Section: Discussionsupporting
confidence: 85%
“…The L-shaped EStim electrodes were attached to the lid of the 6-well plate, and were able to deliver uniform EStim to each individual well. In another study by Du et al [95], a 96-well plate-based high-throughput screening platform was developed for studying the optimal EStim parameters for human neural crest stem cell (NCSC) diferentiation. The EStim electrodes were arranged in a top-down coniguration to generate a vertical electrical ield that can stimulate a larger area.…”
Section: High-throughput Platforms For Studying Cellular Response Tomentioning
confidence: 99%
“…The EStim therapy signiicantly improved the healing of rat femur large defects, with higher bone formation, strength and increased expression of osteogenic genes. The optimal EStim parameters identiied in the study by Du et al [95] was applied to NCSCs that were transplanted in live animals with sciatic nerve injuries. It was found that this EStim protocol signiicantly enhanced the survival rate and diferentiation of the transplanted NCSCs, as well as the overall nerve regeneration.…”
Section: High-throughput Platforms For Studying Cellular Response Tomentioning
confidence: 99%
“…[4][5][6] ES in neural crest stem cell (NCSC) transplantation signicantly enhanced nerve regeneration aer injury and repair. 7 Electrically pre-stimulating SCs (50 mV mm À1 ) promoted 30% more synapse outgrowth relative to co-stimulating both SCs with neurons, suggesting that ES modies SC phenotype. 8 Moreover, the better the development of the role of SCs through ES, the better would be the application in the repair of PNI.…”
Section: Introductionmentioning
confidence: 98%